Advancing climate-smart financial solutions for smallholder farmers: Lessons from the CGIAR Climate Resilience Initiative - Timu, Anne G.; Laborte, Alice; Attoh, Emmanuel M. N. A. N.; Kikulwe, Enock; Kiundu, Paul; Guo, Zhe; Mayanja, Brian; Mbithi, Anthony; Sartas, Murat; Vyas, Shalika; You, Liangzhi (Bioversity International and the International Center for Tropical Agriculture, 2024)
Smallholder farmers in low- and middle-income countries face climate-related risks that increase their income volatility and compromise their well-being. The CGIAR Initiative on Climate Resilience (ClimBeR) has developed and implemented a suite of innovative instruments aimed at transforming the climate adaptation capacity of smallholder farmers. This brief examines the potential of these bundled financial solutions in enhancing smallholder farmers' resilience to climate risks and documents ClimBeR's experience in implementing and scaling these instruments.